2020
DOI: 10.18805/ijar.b-3859
|View full text |Cite
|
Sign up to set email alerts
|

Body Condition Scoring in Dairy Cows - A Conceptual and Systematic Review

Abstract: As herd sizes have increased in the last decades due to commercialization of dairy sector, computer monitoring solutions, which provide fast and accurate evaluation of body condition score, gain more and more importance. The main reasons that discourage the use of traditional BCS estimation techniques are the lack of computerized reports, its subjectivity in the judgment, observational variations and time consuming on farm training of technicians. Moreover, measurement on a cow must be collected every 30 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The positive relation between BCS and body weight was also reported by Yildiz et al (2011) and Tariq et al (2013). Buffaloes of BCSc above 3.5 with significantly higher body weights showed better reproductive performance compared to BCSc groups below 3.5 with less body weights which was in agreement with Gomez et al (2018) and Paul et al (2020).…”
Section: Body Weightssupporting
confidence: 90%
“…The positive relation between BCS and body weight was also reported by Yildiz et al (2011) and Tariq et al (2013). Buffaloes of BCSc above 3.5 with significantly higher body weights showed better reproductive performance compared to BCSc groups below 3.5 with less body weights which was in agreement with Gomez et al (2018) and Paul et al (2020).…”
Section: Body Weightssupporting
confidence: 90%
“…CG is a strong single variable for predicting body weight in limited rearing systems in smallholder farmers (Katongole et al 2013). Several studies have reported a high correlation between CG and body weight, which is generally used to assess productivity in heifers, as an indicator of growth, body calculation, puberty, and date of insemination (Paul et al 2020). Average CG of Bali cow with a BCS of 2,3, and 4 at SPR Kuamang Abadi ranged from 150.6 cm to 167.2 cm (Table 4).…”
Section: Chest Girthmentioning
confidence: 99%
“…Our results were in agreement with de Souza et al (2017) who showed that the BCS was not affected by the supplement treatments. The BCS of cattle indicates a good index of subcutaneous fat, such as rump fat thickness although the LW showed a low correlation with both BCS and rump fat thickness (Ayres et al 2009;Paul et al, 2020).…”
Section: Intakes Liveweight Gain Hip Height Gain and Body Condition S...mentioning
confidence: 99%